Genetics and Pathophysiology of Neurodegeneration with Brain Iron Accumulation (NBIA) - Susanne A. Schneider; Petr Dušek; John Hardy; Ana Westenberger; Joseph Jankovic; Kailash P. Bhatia (2013)
Our understanding of the syndromes of Neurodegeneration with Brain Iron Accumulation (NBIA) continues to grow considerably. In addition to the core syndromes of pantothenate kinase-associated neurodegeneration (PKAN, NBIA1) and PLA2G6-associated neurodegeneration (PLAN, NBIA2), several other genetic causes have been identified (including FA2H, C19orf12, ATP13A2, CP and FTL). In parallel, the clinical and pathological spectrum has broadened and new age-dependent presentations are being described. There is also growing recognition of overlap between the different NBIA disorders and other diseases including spastic paraplegias, leukodystrophies and neuronal ceroid lipofuscinosis which makes a diagnosis solely based on clinical findings challenging. Autopsy examination of genetically-confirmed cases demonstrates Lewy bodies, neurofibrillary tangles, and other hallmarks of apparently distinct neurodegenerative disorders such as Parkinson's disease (PD) and Alzheimer's disease. Until we disentangle the various NBIA genes and their related pathways and move towards pathogenesis-targeted therapies, the treatment remains symptomatic. Keywords: Ceramide, dystonia, iron, NBIA, parkinsonism, MPAN, PKAN, PLA2G6